Effects of creative drama strategies on students' visual perception and attitudes toward learning visual art - Cruz, Martin Jerome G. Goli (College of Education, University of the Philippines Diliman, 2021)
Entering the 21st century, the pedagogy of Philippine visual arts education may evolve to fit the students of Generation Z who are digital mavens adept in technology. The Department of Education, through the Republic Act 10533 series of 2012, supports the new emerging trends in teaching visual arts in the 21st, believing that these are essential in developing skills of the 21st century skills of Grade 7 Filipino students. Certain studies propose that kinesthetics instruction, such as creative drama strategies can help develop art skills such as visual perception and imagination skills through engaging creative drama activities. This research aimed to determine the effectiveness of the visual arts program in enhancing the visual perception skills and possibly changing h the attitudes of Grade 7 co-education students towards learning visual arts at a private progressive school during the school year 2019-2020. Using the Attitude Scale for Art Experienced in Schools (ASEAS) (Pavlou & Kambouri, 2007) and Vividness Visual Imagery Questionnaire (VVIQ) (Marks, 1973) for a group of thirty-eight Grade 7 students for six weeks, the results of the study showed that performance-based and game-based creative drama strategies affected improvement visual perception skills and art attitudes. The [paired sample T-test results showed a statistical significant difference in Grade 7 students' attitudes towards learning visual arts before and after implementing the visual arts program. In contrast, there is no statistically significant difference in Grade 7 students' visual perception skills after implementing the visual arts program. However, qualitative data indicate that there is an improvement in Grade 7 students' visual perception skill. Finally, evidence showed that the visual arts program using creative drama as a teaching strategy helped create a learning environment that fostered meaningful and collaborative visual art experiences that nurtured Grade 7 students' art skills and positive attitudes towards appreciating and learning visual arts.